2019
DOI: 10.2174/1574892814666190514104035
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Disulfiram as An Anti-Cancer Agent: Updated Review on Literature and Patents

Abstract: Background: Despite years of success of most anti-cancer drugs, one of the major clinical problems is inherent and acquired resistance to these drugs. Overcoming the drug resistance or developing new drugs would offer promising strategies in cancer treatment. Disulfiram, a drug currently used in the treatment of chronic alcoholism, has been found to have anti-cancer activity. Objective: To summarize the anti-cancer effects of Disulfiram through a thorough patent review. Methods: This article reviews molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 122 publications
1
56
0
Order By: Relevance
“…174,175 In the past years, disulfiram has attracted increasing attention for its anticancer activity both as monotherapy and combinational therapies. 176 Notably, numerous studies have reported on mechanisms of action of disulfiram that are closely associated with ALDH-related processes of cellular metabolism. For example, Tacconi et al identified disulfirammediated acetaldehyde metabolism as a potential therapeutic target for BRCA1/2-deficient cancer cells, resulting from endogenous acetaldehyde-induced DNA damage.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…174,175 In the past years, disulfiram has attracted increasing attention for its anticancer activity both as monotherapy and combinational therapies. 176 Notably, numerous studies have reported on mechanisms of action of disulfiram that are closely associated with ALDH-related processes of cellular metabolism. For example, Tacconi et al identified disulfirammediated acetaldehyde metabolism as a potential therapeutic target for BRCA1/2-deficient cancer cells, resulting from endogenous acetaldehyde-induced DNA damage.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…DTC-metal complexes have a relatively long half-life and are widely distributed throughout the body, including the gastrointestinal tract. Therefore, in order to achieve adequate levels, ZnDTC is safely given in vivo as oral disulfiram plus zinc gluconate (31,32,(35)(36)(37)(38). Entamoeba histolytica causes an inflammatory diarrhea termed amebic colitis (10).…”
Section: Zndtc Has Potent Activity Against E Histolytica In a Mouse mentioning
confidence: 99%
“…Disulfiram, an alcohol-abuse drug, was found to have anti-cancer activity and several mechanisms of its action were described [40]. Disulfiram triggered oxidative stress by the generation of reactive oxygene species and led to apoptosis in different cancer types [41,42,43].…”
Section: Discussionmentioning
confidence: 99%